EDUCATION THROUGH THEATRE: HOW THE CHILDREN DESERVE - DIDAR MUHAMMAD (CenRaPS Journal of Social Sciences, 2019)
Theatre is known for entertainment but that is not the end. Theatre gives messages; it teaches the young and old through its interactive and communicative action method, easily called learning by doing. Children should not be out of this avail of pedagogy because Child Education is the potential area for entertainment education. Co-curricular Activities are the fundamental elements of teaching. These activities would be more effective if we retouch and modify by Theatrical Method. As the children love to learn by doing, thus they love the text. This paper shows how the teaching method children deserve, how this strategy of education through theatre helps them to love the textbook.